PENGARUH LAMA PERENDAMAN DAN KONSENTRASI GIBERELIN TERHADAP VIABILITAS DAN PERTUMBUHAN AWAL MELON (Cucumis melo L.): - - Widyana Rahmatika; Aimatul Mardiyah; Tri Handayani; Retno Dwi Andayani; Nur Fitriyah; Yushi Mardiana (Innofarm : Jurnal Inovasi Petanian, 2026)
Melon (Cucumis melo L.) is a horticultural commodity with high economic value whose cultivation success is greatly influenced by seed quality and the success of the germination phase. A common problem is the low speed and uniformity of seed germination, which can inhibit early plant growth. This study aims to determine the effectiveness of gibberellin (GA₃) concentration and seed soaking duration on germination and early growth of melon plants. The study was conducted using a factorial experimental design consisting of several levels of gibberellin concentration and seed soaking duration. The parameters observed included maximum growth potential, germination rate, plant length, and number ofleaves. The results showed that gibberellin concentration treatment affected the maximum growth potential of melon seeds, while soaking duration significantly affected germination rate with the best soaking time at 6 hours. However, gibberellin concentration treatment and soaking duration did not significantly affect plant length and number of leaves in the early growth phase. The interaction between gibberellin concentration and soaking duration also did not show a significant effect on all observed parameters. Based on the research results, it can be concluded that the use of gibberellin through seed soaking plays a greater role in increasing viability and the germination process compared to the initial vegetative growth of melon plants.